Incidence and nature of adverse drug events in paediatric intensive care units: A prospective multicentre study. Issue 5 (8th December 2021) - Alghamdi, Anwar A.; Keers, Richard N.; Sutherland, Adam; Hann, Mark; Gray, Jennifer; Mason, Graham; Isaac, Rhian E.; Ashcroft, Darren M.
Abstract : Aims: The aim of this study was to assess the incidence, nature, preventability and severity of adverse drug events (ADEs) across three paediatric intensive care units (PICUs) in England. Methods: A prospective observational cohort study was conducted across three PICUs over a three‐month period during 2019. Included patients were aged ≤18 years and stayed in PICU for a minimum of 24 hours. Identification of suspected ADEs was performed by trained PICU pharmacists. A multidisciplinary expert panel assessed causality, preventability and severity of events. Results: A total of 302 patients were included and 62 ADEs were confirmed (definite/probable causality). One in six patients experienced one or more ADEs. The estimated incidence of ADEs were 20.5 per 100 patients (95% CI 15.3–27.5) and 16.7 per 1000 patient‐days (95% CI 9.3–29.9). The majority of ADEs were judged preventable by the expert panel (36/62, 58.1%). ADEs were commonly involved with medicines prescribing (29/62, 46.8%) and caused temporary patient harm (42/62, 67.7%). Medications for the central nervous system (14/62, 22.6%), infections (13/62, 20.9%) and cardiovascular system (12/62, 19.4%) were commonly implicated with ADEs. Multivariable analysis revealed that patients who stayed in PICU for ≥7 days (OR 6.29, 95% CI 2.42–16.32) were more likely to experience an ADE compared to patients with a stay of 1–6 days. Conclusion: ADEs are common in English PICUs and most of them may be preventable. There is a strong association between ADE occurrence and duration of PICU stay, which represents a target for remedial interventions. Exploring contributory factors of preventable ADEs is now necessary to inform preventive policies.